Behavior of Hydrogen and Nitrogen in Tungsten, as Divertor Wall of a Fusion Reactor - Beneitez, Sergio; Gervasoni, Juana Luisa; Furnari, Juan Carlos (David Publishing Company, 2018)
Fil: Beneitez, Sergio. Comisión Nacional de Energía Atómica; Argentina